1978
DOI: 10.1002/ar.1091910106
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic distribution of nerves in the rat

Abstract: The intrahepatic distribution of nerves in the rat was studied using neurohistochemical and electron microscopic methods. Innervation was restricted primarily to vessels in the portal space and hilus. Both adrenergic and cholinergic fibers were observed in the adventitia of hepatic arteries, and to a lesser extent adjacent to portal veins. Some of the cholinergic fibers, however, were not contiguous with the vasculature. Near the hilus many of these fibers were associated with ganglia while peripherally some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
1
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 31 publications
4
80
1
1
Order By: Relevance
“…The relative liver weight showed a similar pattern of change in the hepatic vagotomized rats and the controls, but comparison of the relative liver weight 7 days after surgery between the groups showed a significant difference in the value and the weight was lower in the vagotomized rats than in the controls (p<0.05, n=6). However, this difference disappeared 14 Changes in food and water intakes in the hepatic branch vagotomized and the control groups were also examined ( Figure 3). The total water intake (Mean + SEM) during the first 7 days after the denervation was 142.7 + 9.8 (n 6) ml in the controls, while it was 154.3 + 16.9 (n 6) ml in the vagotomized rats, indicating no significant difference between the two values.…”
Section: Resultsmentioning
confidence: 99%
“…The relative liver weight showed a similar pattern of change in the hepatic vagotomized rats and the controls, but comparison of the relative liver weight 7 days after surgery between the groups showed a significant difference in the value and the weight was lower in the vagotomized rats than in the controls (p<0.05, n=6). However, this difference disappeared 14 Changes in food and water intakes in the hepatic branch vagotomized and the control groups were also examined ( Figure 3). The total water intake (Mean + SEM) during the first 7 days after the denervation was 142.7 + 9.8 (n 6) ml in the controls, while it was 154.3 + 16.9 (n 6) ml in the vagotomized rats, indicating no significant difference between the two values.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies have revealed, many unmyelinated nerves running in the portal tract along the interlobular arteries, veins and biliary ductules (portal triads) (SUTHERLAND, 1964;UNGVARY and DONATH, 1969;ANUFRIEW et al, 1973;SKAARING and BIERRING, 1976;FORSSMANN and ITO, 1977;REILLY et al, 1978;MCCUSKEY, Fig. 16.…”
Section: Discussionmentioning
confidence: 99%
“…Since the light microscopic study on the Innervation of mammalian liver carried out by RIEGLE (1928) with the silver impregnation method, many investigations have been carried out to elucidate the nature of nerves supplying the liver with a variety of methods: not only electron microscopy but also histochemistry for cholinesterase, fluorescence method, autoradiography using 3H-noradrenalin, and chemical denervation of sympathetic nerves with 6-OH-dopamine (SUTHERLAND, 1964;UNGVARY and DONATH, 1969;ANUFRIEW et al, 1973;SATLER et al, 1974;SKAARING and BIERRING, 1976;FORSSMANN and ITO, 1977;UNO, 1977;REILLY et al, 1978;NOBIN et al, 1978;MCCUSKEY et al, 1979;SAWCHENKO and FRIEDMAN, 1979). YAMADA (1965), ITO and SHIBASAKI (1968) and TSUNEKI and ICHIHARA (1981) utilized transmission electron microscopy (TEM) to study the innervation of the liver in man, the monkey, mouse, several other mammals, birds and lower vertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations